Priming with synthetic oligonucleotides attenuates pressure overload-induced inflammation and cardiac hypertrophy in mice - Velten, Markus; Duerr, Georg D.; Pessies, Thilo; Schild, Julia; Lohner, Ralph; Mersmann, Jan; Zacharowski, Kai; Klaschik, Sven; Hilbert, Tobias; Hoeft, Andreas; Baumgarten, Georg; Meyer, Rainer; et al. (Cardiovascular Research, 2012)
AimsInflammation and Toll-like receptor (TLR) signalling have been linked to the development of cardiac hypertrophy following transverse aortic constriction (TAC). In the present study, we investigated whether pre-treatment with the synthetic TLR9 ligands 1668-thioate or 1612-thioate modulates the progression of TAC-induced cardiac inflammation and hypertrophy.Methods and resultsC57BL/6N-mice were pre-treated with 1668-thioate, 1612-thioate (0.25 nmol/g, i.p.), or phosphate-buffered saline 16 h prior to TAC or sham surgery. Heart-weight/body-weight ratio (HW/BW), cardiomyocyte cell size, cellular macrophage accumulation, myofibroblast differentiation, and collagen deposition were investigated for up to 28 days. Cardiac function was monitored using a pressure-volume catheter and M-mode echocardiography. Inflammatory gene expression in the heart was analysed via gene array, while the time course of mRNA expression of key inflammatory mediators was assessed via RT-qPCR. TAC increased the HW/BW ratio and cardiomyocyte cell size and induced macrophage accumulation, myofibroblast differentiation, and collagen deposition. These changes were accompanied by cardiac inflammation and a significant loss of left ventricular function. Pre-treatment with cytosine-phosphate-guanine (CpG)-containing 1668-thioate attenuated the inflammatory response, the progression of cardiac hypertrophy, and cardiac remodelling, which resulted in a prolonged preservation of left ventricular function. These changes were induced to a smaller extent by the use of the non-CG-containing oligodeoxynucleotide 1612-thioate.ConclusionPre-treatment with 1668-thioate attenuated cardiac hypertrophy following pressure overload, possibly by modifying the hypertrophy-induced inflammatory response, thereby reducing cardiac growth and fibrosis as well as delaying loss of cardiac function. © 2012 The Author.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiac hypertrophy; Cytokine; Cytosine-phosphate-guanine oligodeoxynucleotide; Inflammation; Innate immunity; Transverse aortic constriction